Mobile game development with Corona SDK - Whye, J.A.; Safari eBooks ([S.l.] : InfiniteSkills, 2014)
"In this Mobile Game Development with Corona SDK, expert author J.A. Whye will teach you how to create a mobile game with Corona SDK for iOS or Android. This course is developed for beginners, meaning no prior programming experience is required. You will start by learning about the Lua language, then jump into how to display and animate images. From there, Whye will teach you about tap and touch events and how to use the widget library, including how to make buttons with widgets and create scrolling pictures. This video tutorial will also cover how to create text on the screen, manage a scene with Composer, and saving and loading files."--Resource description page.
Title from resource description page (viewed November 22, 2014).
Presenter, J.A. Whye.
Keywords: Computer games -- Programming; Video games -- Design; Lua (Computer program language); Application software -- Development; Mobile computing -- Programming; Electronic books